2007
DOI: 10.1128/jvi.01287-07
|View full text |Cite
|
Sign up to set email alerts
|

Signal Peptide and Helical Bundle Domains of Virulent Canine Distemper Virus Fusion Protein Restrict Fusogenicity

Abstract: Persistence in canine distemper virus (CDV) infection is correlated with very limited cell-cell fusion and lack of cytolysis induced by the neurovirulent A75/17-CDV compared to that of the cytolytic Onderstepoort vaccine strain. We have previously shown that this difference was at least in part due to the amino acid sequence of the fusion (F) protein (P. Plattet, J. P. Rivals, B. Zuber, J. M. Brunner, A. Zurbriggen, and R. Wittek, Virology 337:312-326, 2005). Here, we investigated the molecular mechanisms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…Although virulent CDV induces only rare syncytia in keratinocytes, we noticed that coexpression of both F wt and H wt glycoproteins in keratinocytes resulted in significant induction of cell-to-cell fusion activity. This could be explained by the fact that (i) in transient-transfection assays, fusion activity occurs in the absence of the matrix protein and/or that (ii) we used an engineered version of F that contains a heterotypic signal peptide; both characteristics have been reported to correlate with enhancement of fusion activity (23,42).…”
Section: Vol 85 2011 Insights Into CDV Multiple-receptor Usage 11243mentioning
confidence: 99%
See 2 more Smart Citations
“…Although virulent CDV induces only rare syncytia in keratinocytes, we noticed that coexpression of both F wt and H wt glycoproteins in keratinocytes resulted in significant induction of cell-to-cell fusion activity. This could be explained by the fact that (i) in transient-transfection assays, fusion activity occurs in the absence of the matrix protein and/or that (ii) we used an engineered version of F that contains a heterotypic signal peptide; both characteristics have been reported to correlate with enhancement of fusion activity (23,42).…”
Section: Vol 85 2011 Insights Into CDV Multiple-receptor Usage 11243mentioning
confidence: 99%
“…Western blotting was performed as described previously (23). Transfected cells were washed twice with cold phosphate-buffered saline (PBS) before the addition of 150 l of lysis buffer (10 mM Tris [pH 7.4], 150 mM NaCl, 1% deoxycholate, 1% Triton X-100, 0.1% sodium dodecyl sulfate [SDS]) with Complete protease inhibitor (Roche Biochemicals).…”
Section: Vol 85 2011 Insights Into CDV Multiple-receptor Usage 11243mentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting. Immunoblotting was performed as previously described (32). Briefly, Vero-SLAM cells were cultured in six-well plates and infected (with the various recombinant CDVs [rCDVs]) at an MOI of 0.02 1 day later or transfected with the different expression vectors.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Shortening of the Fsp results in increased syncytium formation, indicating that this region regulates the F protein function (30). Further studies have shown that this fusion-enhancing effect is observed only in the context of the Onderstepoort strain vaccine, since shortening of the Fsp originating from the wild-type strain A75/17 did not increase cell-cell fusion (19). Extensive folding and formation of RNA secondary structures due to the high GC content of the CDV M-F region may also contribute to the decrease in F gene expression (15).…”
mentioning
confidence: 99%